2021
DOI: 10.1111/tbed.14225
|View full text |Cite
|
Sign up to set email alerts
|

It is everywhere—A survey on the presence of carp edema virus in carp populations in Germany

Abstract: Carp edema virus (CEV) is the causative agent of koi sleepy disease (KSD), a serious gill disease affecting common carp, Cyprinus carpio, and its ornamental variety, koi. After recent detections of the virus in various countries around the world, KSD has emerged as a new global disease in carp. However, the prevalence of the infection in carp populations in a given geographical region has not been studied thoroughly. The present communication reports an investigation into the presence of CEV in carp and koi po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Subsequent cases of CEV infection were documented in populations of koi as well as common carp in the United States (1996, 2005 and 2010) and in Europe: Belgium, Germany (2009), England (2011), Austria, the Czech Republic, France, the Netherlands and Poland (2014) 77 . There are currently two main distinct genogroups of CEV with a different geographical distribution 78 . The European genogroup I is found mainly in farmed or wild common carp in Europe and the USA, while the Asian genogroup II is mainly found in common carp in Asia and is now distributed worldwide in koi due to the global ornamental fish trade 79 .…”
Section: Importance Of Fish Poxviruses In Aquaculturementioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent cases of CEV infection were documented in populations of koi as well as common carp in the United States (1996, 2005 and 2010) and in Europe: Belgium, Germany (2009), England (2011), Austria, the Czech Republic, France, the Netherlands and Poland (2014) 77 . There are currently two main distinct genogroups of CEV with a different geographical distribution 78 . The European genogroup I is found mainly in farmed or wild common carp in Europe and the USA, while the Asian genogroup II is mainly found in common carp in Asia and is now distributed worldwide in koi due to the global ornamental fish trade 79 .…”
Section: Importance Of Fish Poxviruses In Aquaculturementioning
confidence: 99%
“…The European genogroup I is found mainly in farmed or wild common carp in Europe and the USA, while the Asian genogroup II is mainly found in common carp in Asia and is now distributed worldwide in koi due to the global ornamental fish trade 79 . A recent survey showed that both genogroups of the virus are widespread and responsible for multiple outbreaks in cultured and natural populations of common and koi carp worldwide every year 78 . Under experimental conditions, the onset of severe clinical signs leading to mortality occurs within the first week of infection with CEV 31 .…”
Section: Importance Of Fish Poxviruses In Aquaculturementioning
confidence: 99%
See 1 more Smart Citation
“…For example, testing of several shipments of koi, which were sent to German retailers from Japan, showed that asymptomatic fish were repeatedly found positive for the virus (Adamek et al 2016). Furthermore, observation of fish and sequencing of the virus from some fish farmers in Germany showed that over the period of 2014-2021 repeating outbreaks of KSD were caused by the same virus variants, which could hint that the virus persisted in the population (Adamek et al 2021). However, the experimental infections did not confirm a transfer of the virus from survivors of the CEV infections (Adamek et al 2017).…”
Section: Q and Amentioning
confidence: 99%
“…Therefore, the disease associated with a CEV-infection is referred to as Koi Sleepy Disease (KSD). Infections with CEV were found to be widespread in the carp population in European aquaculture (Adamek, Heling, et al, 2022). Even though a limited replication of CEV was observed in explant cultures of carp gills (Adamek et al, 2017), an in vitro cultivation of this virus is not yet possible.…”
Section: Introductionmentioning
confidence: 99%